PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 125 PEKANBARU - Sepri Helmi Sepri Helmi; Hendri Marhadi Hendri Marhadi; H. Lazim N H. Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Background of the problem in this study is the low learning outcomes IPS fourth grade of SDN 125 Pekanbaru, the average grade 65,90, while the value KKM IPS is 70, This study aims to improve learning outcomes IPS fourth grade of SDN 125 Pekanbaru fourth grade through inquiry learning model. The research was conducted pn March 19, 2015 to April 16, 2015 that carried as much as 3 cycles. This thesis presents the results obtained from this study before action replay value with an average of 92,72 Teacher activity the first cycle and the first meeting of 56,37% the second meeting increased to 62,50%. The first meeting meeting of the second cycle 75% and the second meeting increased to 84,37%. The third cycle of the first meeting and the second meeting 93,57% increase to 96,87%. Student activity the first cycle the first meeting with an average of 56,25% and second meeting increased to 62,50%. At the first meeting of the second cycle with an average og 75% and at the second meeting increased to 84,37%. At the first meeting of the third cycle with an average of 90,62% and a second meeting increased to 96,87%. From the above results it is known that the application of inquiry learning model to improve learning outcomes is social studies fourth grade students of SDN 125 Pekanbaru.Key Words: Cooperative Learning Model Inqury, Sosial Studies Student’s Achievement